2013
DOI: 10.3389/fnsys.2013.00093
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral hearing during development: hemispheric specificity in plastic reorganizations

Abstract: The present study investigates the hemispheric contributions of neuronal reorganization following early single-sided hearing (unilateral deafness). The experiments were performed on ten cats from our colony of deaf white cats. Two were identified in early hearing screening as unilaterally congenitally deaf. The remaining eight were bilaterally congenitally deaf, unilaterally implanted at different ages with a cochlear implant. Implanted animals were chronically stimulated using a single-channel portable signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 54 publications
(129 reference statements)
6
71
0
2
Order By: Relevance
“…For instance, our finding of a correlation between the duration of deafness and the N1 latency indicates that longer duration of deafness limits cortical adaptation to the implant signal, at least in the ipsilateral hemisphere to the CI. This supports previous observations of hemispheric specificity of some cortical adaptations (Kral et al, 2013), and is consistent with the finding that longer duration of deafness leads to reduced cortical activation (Green et al, 2005) and poorer auditory discrimination ability with a CI (Sandmann et al, 2010). The limitation in cortical adaptation may be related to physiological deficiencies (Nadol, 1997;Nadol and Wen-Zhuang, 1992;Nadol et al, 1989) and central reorganization during the period of auditory deprivation, in particular a decline in sound memory and a take-over of the auditory cortex by the remaining sensory modalities (Lazard et al, 2013(Lazard et al, , 2012Sandmann et al, 2012).…”
Section: Remarkable Changes In the Contralateral And Ipsilateral Audisupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, our finding of a correlation between the duration of deafness and the N1 latency indicates that longer duration of deafness limits cortical adaptation to the implant signal, at least in the ipsilateral hemisphere to the CI. This supports previous observations of hemispheric specificity of some cortical adaptations (Kral et al, 2013), and is consistent with the finding that longer duration of deafness leads to reduced cortical activation (Green et al, 2005) and poorer auditory discrimination ability with a CI (Sandmann et al, 2010). The limitation in cortical adaptation may be related to physiological deficiencies (Nadol, 1997;Nadol and Wen-Zhuang, 1992;Nadol et al, 1989) and central reorganization during the period of auditory deprivation, in particular a decline in sound memory and a take-over of the auditory cortex by the remaining sensory modalities (Lazard et al, 2013(Lazard et al, , 2012Sandmann et al, 2012).…”
Section: Remarkable Changes In the Contralateral And Ipsilateral Audisupporting
confidence: 87%
“…Specifically, sequentially implanted CI children develop abnormally high lateralization of auditory cortex response contralateral to the stimulated ear when the implantation of the second ear is delayed more than 1.5 years (Gordon et al, 2013). Together with the results from animal studies, these findings point to specific sensitive developmental periods at the ipsilateral and the contralateral hemisphere (Kral et al, 2002(Kral et al, , 2013. Thus, profound deafness beyond these sensitive periods has severe consequences for the development of ipsilateral and contralateral activation after cochlear implantation (Kral and Sharma, 2012).…”
Section: Remarkable Changes In the Contralateral And Ipsilateral Audimentioning
confidence: 86%
“…Differences in developmental time courses of inhibitory and excitatory synapses in the hearing brain [Gao et al, 1999[Gao et al, , 2000 facilitate distinct reorganisations taking place in these two hemispheres in sequential implantations. Consequently, the mechanisms of the reorganisation and the final functional state following early singlesided deafness differ in the two hemispheres -the reorganisations show a strong hemispheric specificity [Kral et al, 2013a]. Such a re-sculptured, asymmetric brain is specialised for the unilateral hearing condition, which may be detrimental for the later use of the initially deaf ear.…”
Section: Aural Reorganisationsmentioning
confidence: 99%
“…The earlier the asymmetry sets in, the larger the effects [Kral et al, 2013a, b]. Interestingly, additionally to a sensitive period for plasticity in the cortex contralateral to the trained ear [for a review, see Kral and Sharma, 2012], the ipsilateral cortex showed even a shorter sensitive period and, within it, more extensive reorganisations [Kral et al, 2013a].…”
Section: Aural Reorganisationsmentioning
confidence: 99%
“…Kral et al [2013] studied white cats suffering from AHL implanted at an early and late age, and compared the subsequent plasticity following chronic CI stimula- 51 tion with local field potentials. The plasticity mechanism was similar at all ages, only the extent of the effect faded with increasing age, with faster progression at the ipsilateral hemisphere.…”
Section: Discussionmentioning
confidence: 99%